2015
DOI: 10.1039/c5cp03787e
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of ionic liquids with noble metal surfaces: structure formation and stability of [OMIM][TFSA] and [EMIM][TFSA] on Au(111) and Ag(111)

Abstract: Aiming at a comprehensive understanding of the interaction of ionic liquids (ILs) with metal surfaces we have investigated the adsorption of two closely related ILs, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [EMIM][TFSA] and 1-methyl-3-octylimidazolium bis(trifluoromethylsulfonyl)imide [OMIM][TFSA], with two noble metal surfaces, Au(111) and Ag(111), under ultrahigh vacuum (UHV) conditions using scanning tunneling microscopy (STM). At room temperature, the ILs form a 2D liquid on either of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
103
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(117 citation statements)
references
References 51 publications
(132 reference statements)
14
103
0
Order By: Relevance
“…who claimed it resulted from the alkyl chain moving from a geometry where it lies parallel to the surface to one in which it is perpendicular to the surface. Such orientations have been seen before, for various ionic liquids on other surfaces, using scanning tunneling microscopy . Here we do not observe a shift in binding energy of the C4 peak, suggesting that it does not change conformation in the film thicknesses studies.…”
Section: Figuresupporting
confidence: 87%
See 2 more Smart Citations
“…who claimed it resulted from the alkyl chain moving from a geometry where it lies parallel to the surface to one in which it is perpendicular to the surface. Such orientations have been seen before, for various ionic liquids on other surfaces, using scanning tunneling microscopy . Here we do not observe a shift in binding energy of the C4 peak, suggesting that it does not change conformation in the film thicknesses studies.…”
Section: Figuresupporting
confidence: 87%
“…Such orientations have been seen before,f or various ionic liquids on other surfaces, using scanning tunneling microscopy. [16,18,21,22,24,27] Here we do not observe as hift in binding energy of the C4 peak, suggesting that it does not change conformation in the film thicknesses studies. NEXAFS data discussed below suggest the imidazolium ring lies perpendicular to the surfacei nt he 4 film, which is consistent with the lower binding energies of C1, C2 and C3 in the 4 film.…”
mentioning
confidence: 46%
See 1 more Smart Citation
“…In recent years numerous efforts have gone toward understanding the complex structure of ILs at the solid-liquid interface using both theoretical approaches6789101112 and experimental methods such as scattering techniques131415, sum-frequency generation161718, surface-force apparatus19202122232425, and scanning probe techniques. For the latter, scanning tunneling microscopy (STM)2627282930313233343536 and dynamic3738394041 and static42434445464748495051 atomic force microscopy (AFM) approaches have made large progress towards imaging the ion layers in two and three dimensions at neutral and charged surfaces such as mica, silica, gold, and highly-oriented pyrolytic graphite (HOPG). Scanning probe microscopy based techniques offer the advantage of high spatial resolution in three dimensions compared to other techniques, allowing for the ion structure to be visualized in a 3D manner, as opposed scattering techniques and SFA where the response is averaged over large areas.…”
mentioning
confidence: 99%
“…Owing to its high decomposition temperature, very low vapor pressure, and a large stability window ranging from −2.5 to 3.0 V versus Ag/AgCl (about 0–5 V vs. Li/Li + ), [BMP][TFSI] is a very promising candidate for LIBs. Special interest was placed on the interactions at the substrate|IL interface under UHV conditions by using several model substrates, for example, single‐crystalline metal surfaces, oxide surfaces, and highly oriented pyrolytic graphite . The above studies, which were conducted in the absence of an applied potential and which focused on the structure formation and the decomposition of the ionic liquid, clearly demonstrated that the chemical interaction with the substrate surface and/or with the added lithium is sufficient to cause decomposition of the IL.…”
Section: Introductionmentioning
confidence: 99%